An exploratory study on the teaching of pre-reading skills to third-year non-English-major students using New Headway Pre-Intermediate textbook at a university in Hanoi: . M.A Thesis - Lê, Thị Hồng Vân (ĐHNN, 2017)
M.A. Thesis -- ĐHNN. Vietnam National University, Hanoi, 2014